A pH-responsive stellate mesoporous silica based nanophotosensitizer for in vivo cancer diagnosis and targeted photodynamic therapy. (14th November 2018) - Lin, Ai-Lan; Li, Song-Zi; Xu, Cai-Hong; Li, Xing-Shu; Zheng, Bi-Yuan; Gu, Jun-Jie; Ke, Mei-Rong; Huang, Jian-Dong
Abstract : A novel stellate mesoporous silica-based pH-responsive nanophotosensitizer can be localized and specifically activated at tumor site for cancer diagnosis and targeted PDT. Abstract : Development of a photosensitizer that can achieve tumor specificity, improve therapeutic efficacy, and reduce side effects remains a challenge for photodynamic therapy (PDT). In this work, a pH-sensitive activatable nanophotosensitizer (SMSN–ZnPc1) has been elaborately designed, which could be readily prepared by using a functionalized zinc(ii ) phthalocyanine (ZnPc) to conjugate with stellate mesoporous silica nanoparticles (SMSNs) through an acid-sensitive hydrazone bond. Meanwhile, a non-activatable analogue SMSN–ZnPc2 has also been prepared as a negative control. The fluorescence emission and singlet oxygen generation of the photosensitizer are essentially quenched in the intact nanophotosensitizer. However, these properties of SMSN–ZnPc1 can be restored greatly both in acidic solutions and at the cellular level. More importantly, after intravenous administration, SMSN–ZnPc1 can also be selectively activated at the tumor site and exhibit efficient tumor growth inhibition in S180 rat ascitic tumor-bearing KM mice with negligible systemic toxicity. It thus may serve as a promising nanoplatform for cancer diagnosis and targeted PDT.